2023
DOI: 10.3390/jpm13030516
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of SAPHO Syndrome Complicated with Ankylosing Spondylitis by Secukinumab: A Case Report

Abstract: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is characterized by a wide range of dermatological and musculoskeletal manifestations, and its outcome has recently been improved greatly by optimizing management. However, the treatment strategies are not standardized and require further refinement. Secukinumab, a fully human monoclonal antibody targeting IL-17A, is approved for the treatment of autoimmune psoriasis, psoriatic arthritis (PsA), and ankylosing spondylitis (AS). Here, a 53-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Despite a limited response to traditional treatment regimens and adalimumab, both skin and osteoarticular symptoms improved after switching to secukinumab. 18 Cheng et al found that in patients with SAPHO syndrome, secukinumab demonstrated a higher improvement rate in cutaneous symptoms compared to osteoarticular symptoms. 19 This difference may be attributed to the involvement of distinct inflammatory pathways in cutaneous and osteoarthritis symptoms among patients with SAPHO syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a limited response to traditional treatment regimens and adalimumab, both skin and osteoarticular symptoms improved after switching to secukinumab. 18 Cheng et al found that in patients with SAPHO syndrome, secukinumab demonstrated a higher improvement rate in cutaneous symptoms compared to osteoarticular symptoms. 19 This difference may be attributed to the involvement of distinct inflammatory pathways in cutaneous and osteoarthritis symptoms among patients with SAPHO syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers have suggested that SAPHO syndrome can be classified as a form of spondyloarthritis, a potential transitional stage between ankylosing spondylitis (AS) and psoriatic arthritis 2,3 . Both SAPHO syndrome and spinal arthritis affect the axial and sacroiliac joints in a similar manner, exhibiting shared characteristics and even instances of co‐occurrence 4,5 . SAPHO syndrome may be associated with the HLA‐B27 gene 2 .…”
mentioning
confidence: 99%